Recent developments regarding periostin in bronchial asthma - Kenji Izuhara; Hisako Matsumoto; Shoichiro Ohta; Junya Ono; Kazuhiko Arima; Masahiro Ogawa (Allergology International, 2015)
Although it is currently recognized that bronchial asthma is not a single disease but a syndrome, we have not yet made use of our new understanding of this heterogeneity as we treat asthma patients. To increase the efficacy of anti-asthma drugs and to decrease costs, it is important to stratify asthma patients into subgroups and to develop therapeutic strategies for each subgroup. Periostin has recently emerged as a biomarker for bronchial asthma, unique in that it is useful not in diagnosis but in categorizing asthma patients. We first found that periostin is a novel component of subepithelial fibrosis in bronchial asthma downstream of IL-13 signals. Thereafter, it was shown that periostin can be a surrogate biomarker of type 2 immune responses, the basis of the notion that a detection system of serum periostin is potentially a companion diagnostic for type 2 antagonists. Furthermore, we have recently shown that serum periostin can predict resistance or hyporesponsiveness to inhaled corticosteroids, based on its contribution to tissue remodeling or fibrosis in bronchial asthma. Thus, serum periostin has two characteristics as a biomarker for bronchial asthma: it is both a surrogate biomarker of type 2 immune responses and a biomarker reflecting tissue remodeling or fibrosis. We can take advantage of these characteristics to develop stratified medicine in bronchial asthma.